The patterns and influencing factors of help-seeking decisions among women survivors of intimate partner violence in China - Hu, Ran (Journal of family violence, 2021)
Although there has been a growing body of empirical research that examines the prevalence rates of intimate partner violence (IPV) and associated factors in Chinese societies, few studies have examined IPV survivors’ help-seeking patterns. Drawing on data from a nationwide survey among the general public in mainland China, the present study sought to investigate help-seeking decisions and associated factors among Chinese women survivors of IPV. The sample consisted of 488 IPV survivors who self-identified as heterosexual women in China. Logistic regression analyses were conducted to identify factors influencing participants’ help-seeking decisions (help-seeking versus non-help-seeking) and non-help-seeking reasons. A latent class analysis (LCA) was used to explore help-seeking patterns among those who sought help. Multinomial logistic regression analyses, as part of the 3-step LCA approach, were employed to locate significant factors associated with distinct help-seeking patterns identified in the LCA. Over two-thirds of the survivors (73.4%) did not seek help. Among the 26.6% of survivors who sought help, the majority sought support from family and friends, rather than professional services. The main reasons for not seeking help include (a) the belief that they could handle the situation by themselves, (b) not knowing to whom they could turn for help, and (c) the belief that the violence experienced was not severe. IPV type and several relationship-related factors stood out as key predictors for different help-seeking decisions. Implications for future research and practice in the context of China are discussed.